'n Empiriese ondersoek na preekvoorstelle oor Ou-Testamentiese tekste in die leesrooster van 2005 - J. Janse van Rensburg (Acta Theologica)
After examining the basic principles for preaching from the Old Testament in a previous article, this article endeavours to investigate a sample of the current state of preaching from the Old Testament. A phenomenological assessment of sermons from the Lectionary of BUVTON (2005) serves as study example. The aim of the research is to determine whether sermons from the Old Testament deals responsibly with the many pitfalls explained in the first article and so often found in preaching from the Old Testament.